TGF-βMERUPAKAN MEDIATOR IMUNOSUPRESI DARI SEL T CD4 + CD25 + IN VITRO - Endharti, Agustina Tri (Jurnal Kedokteran Brawijaya, 2007)
Naturally the existency of regulatory T cells are represented by CD4+CD25+T cells. Those cells have been identified as a population of immuno-regulatory T cells, which mediated suppression of CD4+CD25+T cells by cell–cell contact. In the effectors phase the function of CD4+CD25+T regulatory T cells through the involvement of certain suppressive cytokines, such as TGF-β. In this study, we demonstrated that CD4+CD25+ cells produced high levels of Transforming Growth Factor-β (TGF-β) compared with CD4+CD25-T cells when stimulated by plate-bound anti-CD3 andsoluble anti-CD28. We observed that suppression ability of those cells could be abolished by the presence of anti–TGF-β. Finally, we found that stimulated CD4+CD25+T cells but not CD4+CD25-T cells express high and persistent levels of TGF-β. This finding strongly suggests that CD4+CD25+T cells exert immuno-suppression by cell–cell surfaces interaction involved cell of TGF-β. Keyword: Sel T CD4+CD25+, TGF-β, immunosupresion